Fractal and wavelet image compression techniques - Welstead, Stephen T., 1951- (SPIE Optical Engineering Press, 1999)
Interest in image compression for internet and other multimedia applications has spurred research into compression techniques that will increase storage capabilities and transmission speed. This tutorial provides a practical guide to fractal and wavelet approaches--two techniques with exciting potential. It is intended for scientists, engineers, researchers, and students. It provides both introductory information and implementation details. Three Windows-compatible software systems are included so that readers can explore the new technologies in depth. Complete C/C++ source code is provided, enabling readers to go beyond the accompanying software. The mathematical presentation is accessible to advanced undergraduate or beginning graduate students in technical fields.
Keywords: Image processing -- Digital techniques.; Image compression -- Mathematics.; Fractals.; Wavelets (Mathematics); elektronické knihy; electronic books